Morpholinyl silicon phthalocyanine nanoparticles with lysosome cell death and two-photon imaging functions for in vitro photodynamic therapy of cancer cells - Yu, Hongjie; Chen, Jianling; Chen, Xiuqin; Zhang, Tiantian; Li, Yuyang; Chen, Kuizhi; Peng, Yiru; Chen, Linying (Frontiers in Bioengineering and Biotechnology, 2023)
The lysosome is an important target for realizing antitumor therapy. Lysosomal cell death exerts significant therapeutic effects on apoptosis and drug-resistance. The development of lysosome-targeting nanoparticles to obtain efficient cancer treatment is challenging. In this article, nanoparticles composed of DSPE@M-SiPc and possessing bright two-photon fluorescence, lysosome targeting ability, and photodynamic therapy multifunctionalities are prepared by encapsulating morpholinyl-substituted silicon phthalocyanine (M-SiPc) with 1,2-distearoyl-sn-glycero-3-phosphoethanolamine-N-[methoxy(poly(ethylene glycol))-2000] (DSPE). Two photon fluorescence bioimaging showed that M-SiPc and DSPE@M-SiPc mainly locate in lysosomes after cellular internalization. Upon irradiation, DSPE@M-SiPc effectively generates reactive oxygen species and damages the function of lysosome, subsequently leading to lysosomal cell death. DSPE@M-SiPc is a promising photosensitizer for cancer treatment.